Quantifying the role of mangroves in carbon sequestration in Qatar - Fabiha Sadaf Hussain; Hazrat Bilal; Tareq Al-Ansari (Ecological Informatics)
Mangrove forest ecosystems are globally recognized for their role in mitigating climate change through carbon dioxide sequestration. However, the carbon storage potential of mangroves forests in hot-arid regions, such as Qatar, remains underrepresented in global carbon accounting, limiting their contribution to national climate change and sustainability targets. This study assesses the spatial dynamics and carbon sequestration potential of Avicennia marina species in Al Khor and Al Thakhira using remote sensing and published ecological datasets. Results reveal a spatial expansion of 21.03 %, equivalent to approximately 40 ha, between 2014 and 2023. The current mangrove forest cover is estimated to store 185,641.66 Mg CO₂ equivalent, with an additional 8983.4 Mg CO₂ equivalent sequestered over the past decade, representing an annual rate of 998.15 Mg CO₂ equivalent. Under a no-deforestation scenario, carbon stocks could increase by 5988.94 Mg CO₂ equivalent, reaching 191,837.48 Mg CO₂ equivalent by 2030. Projections under sea level rise scenarios suggest a potential expansion of mangrove forests to 1000 ha by 2032 under RCP 2.6. Conversely, RCP 4.5 and RCP 8.5 are associated with significant carbon losses of 78,814.16 Mg and 101,332.5 Mg CO₂ equivalent, respectively, due to mangrove degradation. Although arid-region mangroves sequester less carbon than tropical systems, their ecological resilience to harsh climatic conditions highlights them as stable and important carbon sinks. Therefore, it is important to identify ecologically suitable sites and prioritize best-practice approaches in mangrove management to enhance their carbon sequestration potential.